Pseudoangiomatous hyperplasia of mammary stroma associated with gynaecomastia - Milanezi, MFG; Saggioro, F. P.; Zanati, S. G.; Bazan, Rodrigo [UNESP]; Schmitt, F. C. (British Med Journal Publ Group, 1998)
Aims-To evaluate the prevalence of pseudoangiomatous hyperplasia of mammary stroma in gynaecomastia and its immunohistochemical profile in this setting.Methods-Eighty eight cases of gynaecomastia recovered from the files of the department of pathology, Botucatu School of Medicine from 1976 to 1996 were studied. In the cases associated with pseudoangiomatous hyperplasia of mammary stroma, immunoreactivity for cytokeratins (CAM 5.2), vimentin, CD34, factor VIII related antigen, and the oestrogen and progesterone receptors were studied.Results-Pseudoangiomatous hyperplasia of mammary stroma was found in 21 of 88 cases of gynaecomastia (23.8%). In all cases, the cells lining the spaces were positive for vimentin, whereas CAM 5.2 and factor VIII related antigen were consistently negative. Nineteen of the 21 cases showed immunoreactivity for CD34. Ductal epithelial cells were positive for both the oestrogen receptor and the progesterone receptor, whereas stromal cells were negative.Conclusions-Pseudoangiomatous hyperplasia of mammary stroma was present in approximately one quarter of the cases of gynaecomastia. This immunohistochemical study confirms the mesenchymal origin of the stromal cells that line the pseudovascular spaces, as has been found in female cases of pseudoangiomatous hyperplasia of mammary stroma.
Keywords: pseudoangiomatous hyperplasia; gynaecomastia; male breast tissue